(untitled) (Baghdad Science Journal, 2011)
The rotation effect upon Morse potential had been studied and the values of the effective potential in potential curves had been calculated for electronic states (X2?+g , B ?u ) K2 molecule. The calculation had been computed for rotational quantum number (J = 5). Also, drawing potential curves for these systems had been done using Herzberg and Gaydon equations. It was found that the values of the dissociation energy which resulting from using Herzberg equation greater than that of Gaydon equation. Besides, it was found that the rotation effect for (X and B) electronic states in Morse potential is very small and in this case may negligible.